U-shaped association between serum Klotho and accelerated aging among the middle-aged and elderly US population: a cross-sectional study - Heng Li; Shuai Miao; Min Zhang; Peng Zhang; Yan-Bin Li; Rui-Sheng Duan (BMC Geriatrics, 2023)
Abstract Background Phenotypic age acceleration, which reflects the difference between phenotypic age and chronological age, is an assessment to measure accelerated aging. Klotho is a protein related to slower aging, but its association with accelerated aging remains unclear. Methods Based on data from the 2007–2010 National Health and Nutrition Examination Survey, phenotypic age was calculated using chronological age and 9 aging-related biomarkers. A total of 4388 participants aged 40 to 79 years with measured serum Klotho and calculated phenotypic age were enrolled. The association between serum Klotho and phenotypic age acceleration was estimated using multivariable linear regression models. The possible nonlinear relationship was examined with smooth curve fitting. We also conducted a segmented regression model to examine the threshold effect. Results The association between serum Klotho and phenotypic age acceleration followed a U-shaped curve (p for nonlinearity < 0.001), with the inflection point at 870.7 pg/ml. The phenotypic age acceleration significantly decreased with the increment of serum Klotho (per SD increment: β -1.77; 95% CI, -2.57 ~ -0.98) in participants with serum Klotho < 870.7 pg/ml, and increased with the increment of serum Klotho (per SD increment:β, 1.03; 95% CI: 0.53 ~ 1.54) in participants with serum Klotho ≥ 870.7 pg/ml. Conclusion There was a U-shaped association between serum Klotho and accelerated aging among the middle-aged and elderly US population.